Semantic and Pragmatic Presuppositions in Postmodern Text - Harmash, Liudmyla; Khalanska, Natalia; Melnyk, Svitlana; Nevelska-Hordieieva, Olena; Razumenko, Iryna (Journal of History Culture and Art Research, 2020)
The article suggests the analysis of literary texts based on the linguistic theory of presuppositions, which is considered to be one of the possible promising approaches to interpreting implicit levels of literary text. The use of this approach is expected to be effective at various communication levels: character-character, narrator-reader, author-reader. The authors use the method of discourse analysis to study the different types of presuppositions and their functioning not only within isolated abstract expressions, but as a part of a broad cultural context. Linguistic methods are combined with a philological method of text interpretation and an intertextual approach, of being subject to consider a random expression in the context of the literary work as a whole. The analysis of presuppositions specificity in the text and the ways of its explication are based on the theory of presuppositions. The methodology of the analysis focuses on identifying presuppositions to establish dominant semantic categories and systemic interaction between them, constituting the artistic picture of the world in Pelevin’s story as a postmodern writing code. Study of the text the presuppositions level helps to clarify the architectonics of the postmodern literary text and to define the ideological constants forming the semantic field of comprehension. The main positions in Pelevin’s work are occupied by such semantic categories as ‘cosmology’, ‘religion’, ‘society’, ‘science’, ‘art’, etc. Their analysis allowed to formulate a meta-subject of postmodern text, which can be defined as ‘rite de passage’. Pelevin’s story is viewed in the context of the dialogue between modernism realized the exhaustion of modern culture, and postmodernism accepted this situation as a given and played the fate tragedy as satyr drama in the best traditions of the ancient theatre: where the modernist hero dies, the postmodernist marginal is able to overcome an irresistible edge.